Wyzwania dla dzisiejszego duszpasterstwa - Marek, Zbigniew (Studia Pastoralne, 2026)
In the face of cultural, economic and social changes a question arises about the shape of the ministry of the word. The article presents a reflection on believers’ religious expectations. One of their expectations is a thorough and exhaustive explanation of the content of the Christian faith. A starting point for such reflection is understanding that Christianity is not ‚the religion of the Book’ but‚ the religion of the word of God’. It should be underlined that the central point of the Christian faith is the person of Triune God, who, in incarnated Christ revealed His mystery. This assumption requires conscious actions, which, on the one hand, will shape the believers’ correct image of God, and, on the other hand, will teach them how to use the sources of faith, which make this image clearer. Another important factor is teaching believers how to use both natural cognition and religious cognition, which together help to discover that the centre of the Christian message is the prophecy of the Kingdom of God initiated in the person of Jesus Christ. Church actively promotes the message of salvation. Catechesis and religious upbringing play an especially important role in spreading this message, as they aim at shaping and upbringing a human being who respects the divine law.